2023
DOI: 10.1038/s41598-023-40714-4
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent variations in BK polyomavirus genome from kidney transplant recipients with persistent viremia

Olga Mineeva-Sangwo,
Elisabet Van Loon,
Graciela Andrei
et al.

Abstract: BK polyomavirus (BKPyV) is a human DNA virus that resides latent in the host’s renal tissue. Reactivation occurs occasionally and in case of kidney transplantation, it can lead to polyomavirus-associated nephropathy (PVAN). Due to the lack of specific antivirals for BKPyV and despite the risk of allograft rejection, reduction of immunosuppression remains the main approach for treating PVAN. Current data suggests that mutations can accumulate over time in the major capsid protein VP1 and can lead to neutralizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…This part of the BKV genome does not appear to be as polymorphic, and PCR will not miss rare genotypes. However, it has recently been shown that this protein can also undergo mutations in rare cases [30]. Despite this potential ambiguity of their test, previous authors have already provided proof of concept by demonstrating high test specificity and sensitivity of over 90% for the diagnostics of BKPyVAN in their test setup [16].…”
Section: Discussionmentioning
confidence: 99%
“…This part of the BKV genome does not appear to be as polymorphic, and PCR will not miss rare genotypes. However, it has recently been shown that this protein can also undergo mutations in rare cases [30]. Despite this potential ambiguity of their test, previous authors have already provided proof of concept by demonstrating high test specificity and sensitivity of over 90% for the diagnostics of BKPyVAN in their test setup [16].…”
Section: Discussionmentioning
confidence: 99%
“…Reducing immunosuppression is still the primary treatment strategy for PVAN, despite the danger of allograft rejection and the lack of specific antivirals for the BK virus. 75 Solomyannyi et al synthesized imidazo[1,2- c ]pyrimidine derivatives and evaluated them against BK polyomavirus for their anticancer potential. Compound 33 , 6-benzyl-8-(methylsulfonyl)-2,6-dihydroimidazo[1,2- c ]pyrimidin-5(3 H )-one, was found to be the most potent molecule of the series with an EC 50 of 0.66 μM [Table 9].…”
Section: Imidazopyrimidines As Antiviral Agentsmentioning
confidence: 99%
“…It has been reported that HPyVs may infect asymptomatic subjects during early childhood, followed by a latency stage. In a peculiar condition of the host, such as immunosuppressive status, HPyVs may reactivate ( 3 , 9 , 10 ). HPyV6, HPyV7, and TSPyV have been associated with rare skin lesions in immunosuppressed patients ( 11 ).…”
Section: Introductionmentioning
confidence: 99%